Cyberfeminisme: Pembebasan Psikologi Perempuan di Ruang Digital - Kholil, Kholil Lur Rochman; Budiantoro, Wahyu (LPPM IAIN Parepare, 2022)
Cyberfeminism emerged as a feminist response to cyberpunk politics, as well as the development of communication technology in the digital space. The agenda of women's liberation in cyberfeminism, echoed by feminists, is to fight subordination. In practice, subordination refers to, among other things, gender inequality. Sexual violence that often afflicts women is often a manifestation of the position of women who are considered weak. Moreover, sexual violence is also targeted online. This is evident from the rise of Online Gender-Based Violence (KGBO). Thus, in this study, the author attempts to describe how cyberfeminism is a way to liberate women from sexual violence. This research uses descriptive qualitative method. The data is obtained through books, papers, or related articles as a support to clearly describe the formula used by feminists. The results of this study indicate that as a way to liberate women in the digital space, it is necessary to have a media with a gender perspective. In addition, feminists and women need to have the power of data as a basis for carrying out the path of liberation.